(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The French philosopher Michel Foucault’s vision of the relationship between the self and the truth is divided into two positions, one of which can be described as negative while the other positive. These positions represent two successive stages of his philosophical life. Critics and many explicator of his philosophy have often viewed them as contradictory approaches. This research represents an attempt to find out the nature of these two positions through an analytical study of some of the Foucault’s spoken in order to establish a link between them depending on the idea that the first position represents the destructive side or the critical aspect of the relationship of the self to the truth. Whereas, the second position represents the constructive aspect towards this relationship in line with the philosophical idea which view that any construction process must be preceded by a process of criticism and displacement -provided that we understand the displacement as a re-questioning of the consistent and assumptive and confiscations that turned under the weight of the sanctification to imagery- on the one hand, and on the other hand explanation the nature of existing relationship between the epistemic and the ethics as two elements contribute in stabilization of self to attainment the truth. تتوزع رؤية الفيلسوف الفرنسي ميشيل فوكو لموضوعة العلاقة بين الذات والحقيقة على موقفين، يمكن وصف الأول بالسلبي بينما الآخر إيجابي، هذان الموقفان يمثلان مرحلتين متتاليتين من حياته الفلسفية غالباً ما نظر إليهما النقاد والعديد من شراح فلسفته على أنهما تعكسان مقاربتين تناقض إحداهما الأخرى. يمثل هذا البحث محاولة للوقوف على طبيعة هذين الموقفين عبر دراسة تحليلية استقصائية لبعض المنطوقات الفوكوية بغرض إيجاد رابط بينهما انطلاقاً من أن الموقف الأول يمثل الجانب الهدام أو لنقل الجانب النقدي من علاقة الذات بالحقيقة في حين أن الموقف الثاني يمثل الجانب البنّاء إزاء هذه العلاقة تماشياً مع الفكرة الفلسفية التي ترى أن أية عملية بناء لا بد أن تسبقها عملية نقد وإزاحة -شريطة أن نفهم الإزاحة على أنها إعادة مساءلة الثوابت والبداهات والمصادرات التي تحولت تحت وطأة التقديس إلى أصنام وأقانيم - هذا من جانب، ومن جانب آخر محاولة تبيان طبيعة العلاقة الكائنة ما بين المعرفي والإتيكي كعنصرين يسهمان في تمكين الذات من بلوغ الحقيقة.